Involvement of mitogen activated kinase kinase 7 intracellular signalling pathway in Sunitinib-induced cardiotoxicity. (1st February 2018) - Cooper, Samantha Louise; Sandhu, Hardip; Hussain, Afthab; Mee, Christopher; Maddock, Helen
Abstract: The tyrosine kinase inhibitor Sunitinib is used to treat cancer and is linked to severe adverse cardiovascular events. Mitogen activated kinase kinase 7 (MKK7) is involved in the development of cardiac injury and is a component of the c-Jun N-terminal kinase (JNK) signal transduction pathway. Apoptosis signal-regulating kinase 1 (ASK1) is the upstream activator of MKK7 and is specifically inhibited by 2, 7-dihydro-2, 7-dioxo-3 H -naphtho[1, 2, 3- de ]quinoline-1-carboxylic acid ethyl ester (NQDI-1). This study investigates the role of ASK1, MKK7 and JNK during Sunitinib-induced cardiotoxicity. Infarct size were measured in isolated male Sprague-Dawley rat Langendorff perfused hearts treated for 125 min with Sunitinib in the presence and absence of NQDI-1. Left ventricular cardiac tissue samples were analysed by qRT-PCR for MKK7 mRNA expression and cardiotoxicity associated microRNAs (miR-1, miR-27a, miR-133a and miR-133b) or Western blot analysis to measure ASK1/MKK7/JNK phosphorylation. Administration of Sunitinib (1 μM) during Langendorff perfusion resulted in increased infarct size, increased miR-133a expression, and decreased phosphorylation of the ASK1/MKK7/JNK pathway compared to control. Co-administration of NQDI-1 (2.5 μM) attenuated the increased Sunitinib-induced infarct size, reversed miR-133a expression and restored phosphorylated levels of ASK1/MKK7/JNK. These findings suggest that the ASK1/MKK7/JNK intracellular signalling pathway is important in Sunitinib-induced cardiotoxicity. The anti-cancer properties of Sunitinib were also assessed using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cell viability assay. Sunitinib significantly decreased the cell viability of human acute myeloid leukemia 60 cell line (HL60). The combination of Sunitinib (1 nM–10 μM) with NQDI-1 (2.5 μM) enhanced the cancer-fighting properties of Sunitinib. Investigations into the ASK1/MKK7/JNK transduction pathway could lead to development of cardioprotective adjunct therapy, which could prevent Sunitinib-induced cardiac injury.